Mitigating Drought Impact in Corn Cultivation Using Different Drip Irrigation Techniaues - Fattah, Mohammed A.; Aziz, Salah A.; Kader, Mohammed S. (Sulaimani Journal for Pure and Applied Sciences, 2020)
The excessive use of irrigation water led to thinking about creating new irrigation techniques to take full advantage of water input, whereby the agricultural drought will be reduced. For this purpose the current study was carried out to adopt modern irrigation techniques by manipulating traditional drip irrigation technique at depth 0, 5, 15, and 30 cm (DI, SDI5, SDI15, SDI30) and basket technique at depth 5, 15, and 30 cm (BT5, BT15, and BT30) for irrigating corn plant under two levels of irrigation for receiving 100% and 65% of depleted water (I1 and I2, respectively). The grain yield and the amount of consumed water were estimated to calculate irrigation water use efficiency (IWUE) and yield response factor (Ky). The cumulative depth of irrigation with precipitation for I1 and I2 were 781 and 606 mm, respectively. The grain yield of corn has been significantly (p ≤ 0.05) influenced by level and technique of irrigation; the level I1 and the technique SDI15 showed the highest values. Also the maximum IWUE among all techniques in both irrigation levels was for SDI15, while the minimum IWUE was for DI. The yield response factor showed no significant difference (p ≤ 0.05) among all techniques except the DI which gave the highest value 1.381, while the lowest value of 1.093 recorded for BT5. In this study, Ky values in all drip irrigation techniques were bigger than one; In this case using degree of soil water stress (Ks) less than 0.74is not preferable and mitigating drought impact in corn cultivation is unsuccessful.
Keywords: Corn grain yield; Irrigation water use efficiency; Yield response factor; Drip irrigation